Gambaran kepuasan pasien pada pelayanan kesehatan di Puskesmas Bahu dan Puskesmas Pineleng - Angelivia Berliani; Margareth Rosalinda Sapulete; Henry Malcom Frank Palandeng (UNIVERSITAS SAM RATULANGI, 2026)
Background: Quality healthcare services are a crucial factor in achieving patient satisfaction. Studies conducted at several public health centers (Puskesmas) in Indonesia show that some patients are still dissatisfied with their services. Aim: To describe patient satisfaction with healthcare services at two Public Health Center: Bahu and Pineleng, based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Methods: This is a quantitative descriptive study using a cross-sectional design. The sampling technique used purposive sampling. Data collection was conducted using a questionnaire. Results: The picture of satisfaction at Bahu Public Health Center for tangible: 37.4% very satisfied, 46.7% satisfied, and 15.9% quite satisfied, reliability: 42.1% very satisfied, 48.6% satisfied, and 9.3% quite satisfied, responsiveness: 61.7% very satisfied, 31.8% satisfied, and 6.5% quite satisfied, assurance: 45.8% very satisfied, 43% satisfied, and 11.2% quite satisfied, empathy: 49.5% very satisfied, 40.2% satisfied, and 10.3% quite satisfied. Meanwhile, at Pineleng Public Health Center, tangible: 50.9% very satisfied, 41.7% satisfied, and 7.4% quite satisfied; reliability: 67.6% very satisfied, 25.9% satisfied, and 6.5% quite satisfied; responsiveness: 71.3% very satisfied, 24.1% satisfied, and 4.6% quite satisfied; assurance: 63% very satisfied, 30.6% satisfied, and 6.5% quite satisfied; empathy: 70.4% very satisfied, 25% satisfied, and 4.6% quite satisfied. Conclusion: The majority of patients at both public health centers were very satisfied and satisfied across all dimensions.